Digipreneur 101: Regenerative Tourism and Bilingual Promotion for Local Community Empowerment in Gorontalo - Danial, Haris; Talib, Rasuna; Dako, Rahman Taufiqrianto; Pakaya, Usman (Penerbit Widina, Widina Media Utama, 2024)
The community service program aims to empower the local community with a focus on sustainable and regenerative tourism development. This program focuses on two main aspects: environmental preservation and sustainable promotion of local potential. The program’s objectives are: 1) Prioritizing a tourism concept that not only promotes sustainability but also strives to restore and improve local ecosystems, 2) This programprovides training to theDunggala community on promoting local tourism potential in two languages (Indonesian and English),3) Towards Digipreneur: Through digitalentrepreneurship training, the Dunggala community is taught how to use digital technology to promote their tourism destinations. The implementation method for the program is designed systematically to effectively achieve the expected goals and outcomes. The activities planned for August and September 2024 aim to empower local communities, especially in rural areas like Dunggala, by combining digital entrepreneurship, sustainable tourism, and creative economy development. The outcomes of this program are: the community becomes capable of managing and promoting tourist destinations with a regenerative approach, improved English communication skills to welcome foreign tourists, enhanced digital literacy, enabling them to become digipreneurs who can adapt to the digital era, and the preservation of the local environment and culture through responsible tourism management.ABSTRAKProgram pengabdian masyarakat bertujuan untuk memberdayakan masyarakat lokal dengan fokus pada pengembangan pariwisata berkelanjutan dan regeneratif. Program ini bertumpu pada dua aspek utama: preservasi (pelestarian) lingkungan serta peningkatan promosi potensi lokal yang berkelanjutan. Tujuan lainnya program ini adalah 1) Regenerative Tourism: Mengedepankan konsep pariwisata yang tidak hanya berkelanjutan; 2) Promosi Potensi Lokal Berbasis Bilingual: Program ini memberikan pelatihan kepada masyarakat Dunggala untuk mempromosikan potensi wisata lokal dalam dua bahasa (Bahasa Indonesia dan Bahasa Inggris); 3) Menuju Digipreneur: Melalui pelatihan kewirausahaan digital, masyarakat Dunggala diajari cara menggunakan teknologi digital untuk mempromosikan destinasi wisata mereka. Metode pelaksanaan program dirancang secara sistematis untuk mencapai tujuan dan hasil yang diharapkan secara efektif. Kegiatan yang direncanakan untuk Agustus dan September 2024 bertujuan untuk memberdayakan komunitas lokal, terutama di daerah pedesaan seperti Dunggala, dengan menggabungkan kewirausahaan digital, pariwisata berkelanjutan, dan pengembangan ekonomi kreatif. Hasil yang diperoleh dalam program ini adalah masyarakat mampu mengelola dan mempromosikan destinasi wisata dengan pendekatan regeneratif, peningkatan kemampuan komunikasi dalam bahasa Inggris untuk menyambut wisatawan asing, peningkatan literasi digital masyarakat, sehingga mereka dapat menjadi digipreneur yang mampu beradaptasi dengan era digital, dan terlestarikannya lingkungan dan budaya lokal melalui pengelolaan pariwisata yang bertanggung jawab.